Allelopathic effects of bioactive aqueous extracts on the growth and development of Solanum lycopersicum L - Tetiana Solodka; Olesia Solodka (Frontiers in Plant Science)
This study examines the allelopathic effects of aqueous seed extracts from Brassica napus L., Mentha piperita L., Passiflora incarnata L., and Sinapis alba L. on the growth and development of Solanum lycopersicum L. The application of the extracts influenced seed germination dynamics and altered the accumulation of photosynthetic pigments. The extract of Sinapis alba L. led to the highest increase in chlorophyll a and b levels, while Brassica napus L. showed the strongest stimulation of seed germination. One-way ANOVA confirmed statistically significant differences between treatments. The results support the potential of selected botanical extracts as natural biostimulants. Further investigation is required to assess their efficiency in field conditions and their interaction with soil microbiota.